Present and future of semantic web technologies: a research statement - Patel, Archana; Jain, Sarika (International journal of computers & applications, 2021)
Semantic web and its technologies have been eyed in many fields. They have the capacity to organize and link data over the web in a consistent and coherent way. Semantic web technologies consist of RDF schema, OWL, and rule and query languages like SPARQL and these technologies will help the various domains to resolve their problems. This review paper starts with analyzing the nature of semantic web and its requirements. We have considered all 10 domains which are closely related to semantic web and its technologies. For a better understanding of the paper, we have separated it into three major contributions. First, we analyze semantic web and those domains that increase the growth of the semantic web. Second, we discuss all domains where semantic web technologies play a vital role. Third, we emphasize those domains that go hand in hand with semantic web technologies. This review paper will be utilized as an unbiased direction for the researchers.